The Dark Side of Regulatory Economics: Evidence from the Salt Import Policy in Post-Soeharto Indonesia - Hidayat, Rahmad; Raman, Asrul (ijd-demos, 2020)
Economics regulation by the state is indeed very necessary to ensure that the pursuit of profit does not conflict with social welfare. That is the reason why regulatory economics becomes really important. However, the context in this paper contradicts with the ideal substance of regulatory economics in which the government proactively provides incentives to remain entrenched monopolistic business practices while taking a dominant role in importing salt commodity through the issuance of a public policy that is more permissive and accommodating to those interests. This paper aims to describe the political dynamics in the formulation and implementation of salt import policy in Post-Soeharto Indonesia which was mainly characterized by the practice of unfair business competition. As descriptive qualitative research, this study utilized in-depth interviews, observation, document tracking, and document analysis techniques in which a number of bureaucrats, entrepreneurs, and salt farmers were used as informants to mine the data. The results of this study show that government intervention through Permendag No. 125/2015 does not reveal a pure orientation of "liberating salt commodity trade from monopolistic business practices", but to satisfy its vested interests and save the sakes of certain importers who were being the important part of its business collusion. Content imperfections, deliberate elimination of substantive obligations, facilitation of rent-seeking and monopolistic business practices, and the impartiality of the regulation’s purpose with the livelihoods of salt farmers in Indonesia become primary impetuses of the resistance of various parties to the dark side of regulatory economics imposed by the government.Regulasi ekonomi oleh negara memang sangat diperlukan untuk memastikan bahwa pengejaran keuntungan tidak bertentangan dengan kesejahteraan sosial. Itulah alasan mengapa ekonomi regulasi menjadi sangat penting. Namun, konteks dalam makalah ini bertentangan dengan substansi ideal ekonomi pengatur di mana pemerintah secara proaktif memberikan insentif untuk tetap mempertahankan praktik bisnis monopolistik sambil mengambil peran dominan dalam mengimpor komoditas garam melalui penerbitan kebijakan publik yang lebih permisif dan akomodatif. untuk kepentingan itu. Makalah ini bertujuan untuk menggambarkan dinamika politik dalam perumusan dan implementasi kebijakan impor garam di Indonesia pasca-Soeharto yang terutama ditandai oleh praktik persaingan usaha tidak sehat. Sebagai penelitian kualitatif deskriptif, penelitian ini menggunakan wawancara mendalam, observasi, penelusuran dokumen, dan teknik analisis dokumen di mana sejumlah birokrat, pengusaha, dan petani garam digunakan sebagai informan untuk menambang data. Hasil penelitian ini menunjukkan bahwa intervensi pemerintah melalui Permendag No. 125/2015 tidak mengungkapkan orientasi murni "membebaskan perdagangan komoditas garam dari praktik bisnis monopolistik", tetapi untuk memuaskan kepentingan pribadi dan menyelamatkan kepentingan importir tertentu yang sedang bagian penting dari kolusi bisnisnya. Ketidaksempurnaan konten, penghapusan sengaja kewajiban substantif, fasilitasi perburuan rente dan praktik bisnis monopolistik, dan ketidakberpihakan tujuan regulasi dengan mata pencaharian petani garam di Indonesia menjadi dorongan utama dari resistensi berbagai pihak terhadap sisi gelap ekonomi regulasi. dipaksakan oleh pemerintah.